Investigating and measuring the impact in efficiency of FinTech operations on integrating Blockchain - Swapnil Sonawane; Amit Nerurkar; Ravindra Sangle; Sanjeev Dwivedi (Utilitas Mathematica, 2025)
This paper looks at how using blockchain technology affects the efficiency of FinTech operations, especially in India. Through detailed quantitative and qualitative analysis, it examines key performance indicators (KPIs) like transaction speed, cost savings, and overall efficiency before and after implementing blockchain. The results show major improvements in these KPIs, indicating blockchain's potential to transform financial services. Insights from industry experts, FinTech leaders, and blockchain specialists add a deeper understanding of blockchain's strategic value and future trends in FinTech. The paper also provides practical advice and best practices for FinTech companies planning to adopt blockchain, aiming to make the integration process smoother and more effective. The study highlights blockchain's ability to enhance security, lower costs, and support financial inclusion, particularly in India's FinTech industry